Os efeitos causados pelo Covid aos empreendedores brasileiros em 2020. - Costa Junior, Edmundo da Silva (Brasil, 2023)
This study, based on data about the pandemic from February 2020 to August 2021, proposed to investigate the economic and financial situation of micro-enterprises and the main public policies of support and their results, in the year of 2020, considered the most expressive temporal reference of the pre, during and post crisis phases. The objectives pursued focused on identifying the situation of the most fragile entrepreneurs and the types of policies adopted. The methodology used in the research was based on secondary data analysis, collected from sources such as SEBRAE and FGV, as well as scientific articles. The study concluded that, despite the dramatic characteristics of the Covid-19 crises, as well as difficulties in institutional alignment and the diversion of financial resources caused by political-ideological problems, the public policies that were being implemented in the country effectively contributed to minimize the negative impacts of the Covid-19 pandemic, especially by expanding the resilience and innovative readaptation capacity of micro-entrepreneurs.